Regulation of recombinant rat tyrosine hydroxylase by dopamine. - Ribeiro, P (1992)
Recombinant rat PC12 tyrosine hydroxylase, also called tyrosine 3-monooxygenase [L-tyrosine, tetrahydropteridine:oxygen oxidoreductase (3-hydroxylating), EC 1.14.16.2], purified from Escherichia coli is in an activated form with a low Km for the tetrahydrobiopterin cofactor and a pH optimum of 6.5. Pretreatment with low levels of the derived product, dopamine, inhibits catalytic activity, increases the Km for the cofactor, and shifts the pH curve towards a more acidic pH optimum. Labeled dopamine binds to tyrosine hydroxylase with high affinity (Kd = 1 microM) but low stoichiometry (r = 0.08 mol/mol of enzyme subunit). The binding of dopamine results in the appearance of a blue-green chromophore with lambda max at approximately 660 nm, which is consistent with the formation of a catecholamine-iron complex. In the absence of dopamine, the recombinant enzyme cannot be further activated by phosphorylation with cAMP-dependent protein kinase, although as much as 1 mol of phosphate is incorporated per mol of subunit. In contrast, the enzyme pretreated with dopamine is activated by phosphorylation in the same fashion and to the same extent as the native hydroxylase. The results suggest that the high-affinity binding of catecholamine products is a pivotal post-translational modification that determines the state of enzyme activation and the response to phosphorylation.